ANALISA KETIDAKPATUHAN PENERAPAN DAN KELENGKAPAN K3 MAHASISWA PADA PRAKTIKUM KOROSI DAN TEKNIK PELAPISAN DI LABORATORIUM PTM UNSRI - Walker Husein, Ridaullah; Wadirin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the level of student non-compliance with the implementation of Occupational Health and Safety (OHS) and the completeness of Personal Protective Equipment (PPE) usage during Corrosion and Coating Engineering practicum activities in the Mechanical Engineering Education Laboratory of Sriwijaya University. The research method used was descriptive quantitative with a percentage approach. Data were collected through questionnaires, observations, and interviews involving 75 students as respondents. The results showed that the level of student non-compliance was categorized as moderate, with a percentage of 52.73%. In detail, the aspect of compliance with OHS implementation was 49.92%, PPE usage was 54.19%, students’ attitudes toward OHS were 53.88%, and risk perception was 52.94%. These results indicate that the implementation of OHS during practicum activities has not been fully optimal. Student non-compliance was identified as being related to PPE usage, students’ attitudes toward OHS, and risk perception during practicum activities.